Assessment of group formation methods on performance in group-based learning activities - Bergtold, Jason S.; Shanoyan, Aleksan (Frontiers in Education, 2024)
Research on teaching and learning has demonstrated many benefits from team- and group-based learning for improving content comprehension and meeting learning outcomes in a wide range of disciplines. We help to expand on this research, by shedding additional light on the impact of group formation decisions on group performance during group learning activities in a higher education classroom setting. Our objective is to assess the impact of different group formation strategies, including random assignment, self-selection, and methods based on individual metrics, such as academic performance and individual skill levels. Using an experimental design approach, we find that GPA-based and math-ability based group formation strategies may provide some additional benefit to group performance on the margin when initially forming groups. Self-selection of groups may be more beneficial after students learn more about each other (e.g. skills sets and work ethic) during the progression of the course. Our study contributes to the literature by providing an assessment of different group formation strategies that are accessible to a wide range of instructors for small to large classes, as well as guidance on use of different group formation strategies within classes, specifically for classes with more quantitative and analytical tasks.